Experimental Investigation of the Тransient Output Impedance of Single Phase On-Grid Inverter - Angelina Tomova; Mihail Antchev (Institute of Advanced Engineering and Science, 2014)
The development of the technologies for connection of the photovoltaic systems to the electrical grid imposed the need of good connection of the interaction between the connecting power converter and the electrical grid. This paper presents research on the output impedance, based on experimental investigation of single-phase on–grid inverter. Its main objective was to identify the unknown output impedance of the commercial on-grid inverter through the waveforms at the point of common coupling (PCC) to the electrical grid, and then perform stability analysis between the inverter, represented by Norton equivalent model, and the grid by verifying the satisfaction of the Nyquist stability criterion. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3590